TRABD maintains mitochondrial homeostasis and protects against ischemia reperfusion-induced renal tubular injury - Duan, Wenqi; Wu, Wenye; Yang, Cui; Zhang, Mei; Li, Xuemei; Tian, Wenmin; Chen, Yang; Zhang, Xinjun (Frontiers in Cell and Developmental Biology, 2025)
Mitochondria serve as hubs for many critical cellular processes, and their functions and dynamics are tightly controlled. TRABD is a Tiki/TraB family protein with unknown function. Here, we characterized TRABD as a novel outer mitochondrial membrane protein. Depletion of TRABD in cells severely impairs mitochondrial respiration and ATP production, inhibits cell growth, increases reactive oxygen species levels. Depletion of TRABD also affects mitochondrial dynamics and mitophagy, possibly through interactions with PGAM5. Knockout of TRABD in mice significantly exacerbates ischemia reperfusion-induced renal tubular injury by promoting mitochondrial fragmentation and damage. Our study identified a novel outer mitochondrial membrane protein and revealed the critical roles of TRABD in mitochondrial dynamics and ischemia reperfusion-induced renal tubular injury.